Experimental and numerical investigations on reliability of air barrier on oil containment in flowing water. Issue 1 (15th June 2015) - Lu, Jinshu; Xu, Zhenfeng; Xu, Song; Xie, Sensen; Wu, Haoxiao; Yang, Zhenbo; Liu, Xueqiang
Highlights: Effective containment distance is proposed to reflect the effectiveness of air barrier. Air pipe configurations affect the performance of air barrier as oil boom. Air flow rate of pipe plays important role on the performance of air barrier. Environmental surface flow affects the effectiveness of oil containment boom. Abstract: Air barriers have been recently developed and employed as a new type of oil containment boom. This paper presents systematic investigations on the reliability of air barriers on oil containments with the involvement of flowing water, which represents the commonly-seen shearing current in reality, by using both laboratory experiments and numerical simulations. Both the numerical and experimental investigations are carried out in a model scale. In the investigations, a submerged pipe with apertures is installed near the bottom of a tank to generate the air bubbles forming the air curtain; and, the shearing water flow is introduced by a narrow inlet near the mean free surface. The effects of the aperture configurations (including the size and the spacing of the aperture) and the location of the pipe on the effectiveness of the air barrier on preventing oil spreading are discussed in details with consideration of different air discharges and velocities of the flowing water. The research outcome provides a foundation for evaluating and/or improve the reliability of a air barrier on preventing spilled oil from further spreading.